Path Analysis of the Effect of Academic Emotions in Academic Achievement of Nursing Students of Zanjan University of Medical Sciences in the 2018-19 Academic Year through the Mediation of the Academic Engagement and Cognitive Strategies - Masoumi Jahandizi H; Hejazi M; Ahmadi MS; Vakili MM (Preventive Care in Nursing and Midwifery Journal, 2018)
Background: Identification of the factors that result in academic achievement and prevent academic failure is of extreme importance due to the effective role of nursing in the health and wellbeing of human beings. Objectives: This study is done with regards to the important role of academic emotions in academic achievement and the double effect of academic engagement mediators and cognitive strategies in the process; Therefore, the focus of this investigation is the influential role of academic emotions in academic achievement of the nursing students of Zanjan University of Medical Sciences through mediation of academic engagement and cognitive strategies. Methods: This research is causal-comparative in nature, covering a statistical population of 178 male and female students of nursing in Zanjan University of Medical Sciences, who were found qualified for this study. Questionnaire was used as an instrument for collection of data, which was then analyzed using SPSS24 and LISREL 8.8. Results: The findings showed that academic engagement with a coefficient of 0.58 and cognitive strategies with a coefficient of 0.22 mediated academic achievement and academic emotion. Moreover, the adequacy of the model was above 0.90 through the Goodness-of-Fit Indices. Moreover, the adequacy of the model was proved through such Goodness-of-Fit Indices as the Chi-square test, which equaled 6.12, the six degrees of freedom (6DoF) and the 0.40 level of statistical significance (p). Conclusion: Therefore, it is concluded that mediation of academic engagement and cognitive strategies will enhance effect of academic emotion in academic achievement and the variables have well proved their mediation role